2022
DOI: 10.3389/fphar.2022.891304
|View full text |Cite
|
Sign up to set email alerts
|

Remedial Aspect of Zinc Oxide Nanoparticles Against Serratia Marcescens and Enterococcus Faecalis

Abstract: Zinc oxide nanoparticles (ZnO NPs) have been widely used in biomedical applications due to their high biocompatibility and low toxicity to humans. The present work aimed to investigate the antibacterial effects of different concentrations of ZnO NPs on two opportunistic pathogens, Serratia marcescens and Enterococcus faecalis. The surface interaction between nanoparticles and bacterial cell wall, and the subsequent morphological alterations on the bacterial surface, were examined through Fourier transform infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…In this study, the highest concentrations of the starch-based ZnO-NPs exhibited significantly greater inhibition zones compared to the lowest concentrations. These results were consistent with the previous studies in which higher concentrations of ZnO-NPs showed stronger antimicrobial effects [8] , [25] , [26] . However, some studies showed that the inhibition zone of nanoparticles starts to shrink beyond an optimal concentration [28] , [29] .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the highest concentrations of the starch-based ZnO-NPs exhibited significantly greater inhibition zones compared to the lowest concentrations. These results were consistent with the previous studies in which higher concentrations of ZnO-NPs showed stronger antimicrobial effects [8] , [25] , [26] . However, some studies showed that the inhibition zone of nanoparticles starts to shrink beyond an optimal concentration [28] , [29] .…”
Section: Discussionsupporting
confidence: 93%
“…The MOF-Gel group also displayed antibacterial activity with (P < 0.001) or without (P < 0.001) laser irradiation compared with PBS-Gel group, suggesting that Zn 2+ might cause bacterial death by the damage of bacterial membranes. 45 Interestingly, the group of Ce6@MOF-Gel with Laser showed the best antibacterial effect among all groups (1.21 ± 0.15%, P < 0.05), which was close to that of the positive control penicillin (1.06 ± 0.49%). The significant suppression may be owing to the synergistic antibacterial effect of Zn-MOF combined with PDT in Ce6@MOF-Gel.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…As shown in Figure a,b, the bacterial survival rate in the group of Ce6-Gel with Laser was 34.3 ± 8.61% due to the production of ROS by PDT. The MOF-Gel group also displayed antibacterial activity with ( P < 0.001) or without ( P < 0.001) laser irradiation compared with PBS-Gel group, suggesting that Zn 2+ might cause bacterial death by the damage of bacterial membranes . Interestingly, the group of Ce6@MOF-Gel with Laser showed the best antibacterial effect among all groups (1.21 ± 0.15%, P < 0.05), which was close to that of the positive control penicillin (1.06 ± 0.49%).…”
Section: Resultsmentioning
confidence: 65%
“…In line with these findings, our earlier publication reported a dose-dependent growth inhibition of ZnO NPs on S. marcescens and E. faecalis with more percentage of growth inhibition on E. faecalis with the reported values of 5. 42, 16.69, 23.74, 32.07, 54.73, and 63.50 % compared with 1.34, 5.65, 16.03, 21.73, 32.1 and 51.27 % of growth inhibition on S. marcescens for 5, 10, 20, 40, 80, and 160 μg/ml of ZnO NPs respectively at 24 hours (Djearamane et al 2022).…”
Section: Int Assaymentioning
confidence: 91%
“…The previous publication of the same author (Djearamane et al 2022) studied the surface topology of ZnO NPs using scanning electron microscopy and reported it as the mixed rod and sphericalshaped particles with an average size of 59.1 nm.…”
Section: Characterization Of Zno Npsmentioning
confidence: 99%